Evaluation of anti-microbial activity and minimum inhibitory concentration of Flacourtia jangomas fruits - Rahman, MD. Atikur (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.